eduksi Buta Aksara melalui aplikasi Magguru Mabbaca pada kelompok remaja masjid di Desa Pationgi - Fani Wulandari; Muhammad Safar; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Hasbi Hasbi; Karmila Karmila (Universitas Hamzanwadi, 2022)
Illiteracy is a crucial issue today, especially in Indonesia. The high illiteracy rate in Indonesia reaches 3.56% of the population. One of the most significant illiteracy issues is in Pationgi Village, Patimpeng District. Illiteracy is experienced by many teenagers, especially those who are not in school. The culture of the community also contributes to the high illiteracy rate in Pationgi Village. Most parents have never been to school or tried to get an education, which makes kids reluctant to go to school, leading many people who cannot read or write. The purpose of this community service is to reduce illiteracy through community service activities and the assistance of the Magguru Mabbaca application. Magguru Mabbaca is a mix of data, video, audio, text, and sounds that can be seen and heard on a smartphone. Magguru Mabbaca was developed to allow partners to understand and recognize letters and numbers quickly. Integrating the Bugis language with Magguru Mabbaca will assist the Pationgi Village community, which is still illiterate. Counseling at partner locations, training with two stages of training beginning with the introduction and operation of applications, and assistance to see an increase in partners' knowledge and understanding of reading and arithmetic are all part of the implementation methods. The result of this community service is that partners experience a significant increase in the knowledge component and application of technology, with an increase of 85% and 100%, respectively. This shows that the Magguru Mabbaca application helped partners improve their reading and math skills in a big way. Therefore, Magguru Mabbaca can be a solution for people in South Sulawesi who still have a high quantity of illiterates, which can be reduced by introducing holistic applications.